Blowing the bloody doors off [compact disc, unabridged] : and other lessons in life - Caine, Michael (Hachette Audio, 2018)
The Hollywood legend reveals the wisdom, stories, insights, and skills that life has taught him in his rise from humble origins to the pinnacle of success.